Analisis Peran Pendamping Sosial Program Keluarga Harapan (PKH) Di Kecamatan Sungai Serut - Maulida Eka Putri Sompie (Jurnal Multidisiplin Dehasen (MUDE), 2022)
Family Hope Program social assistants are Indonesian citizens who meet certain qualifications and pass the selection test and are determined through a Decree of the Director of Social Security, Ministry of Social Affairs, RI to provide assistance to PKH participants based on a work contract within a certain period of time. PKH social assistants play a role in carrying out all stages of PKH implementation. The method used in this research is descriptive qualitative research with the research location in Sungai Serut District. Data collection was carried out using observation, interviews, and documentation. The data analysis technique uses data collection, data reduction, data presentation and conclusion drawing. The research aspect was adopted from Role Theory according to Jim Ife (2014) namely the facilitative role, educational role, representative role and technical role and collaborated with Social Minister Regulation No. 1 of 2018 concerning the Family Hope Program, Guidelines for Implementing the PKH 2021 and Technical Guidelines for the Distribution of PKH Non-Cash Social Assistance in 2021. This study aims to determine the role of social assistants for the Family Hope Program in Sungai Serut District. The results showed that PKH social assistants in Sungai Serut District were considered quite good in carrying out facilitative roles, while in educational, representative and technical roles there were still roles that had not been implemented due to several obstacles and others.